Female Rugby Union injuries in New Zealand: A review of five years (2013-2017) of Accident Compensation Corporation moderate to severe claims and costs - King, D.; Hume, P.; Hardaker, N.; Cummins, C.; Clark, T.; Pearce, A. J.; Gissane, C. (Journal of Science and Medicine in Sport, 2019)
Objectives: To provide epidemiological data and related costs for moderate-to-serious and serious injuryclaims for women`s rugby union in New Zealand.Design: A retrospective analytical review of injury entitlement claims for women`s rugby from 2013 to 2017. Methods: Data were analysed by year of competition, age, body site and injury type for total and moderate-to-severe (MSC) Accident Compensation Corporation (ACC) claims and costs.Results: Over 2013 to 2017 there were 26,070 total claims for female rugby union costing $18,440,812[AD$16,956,998]. The 15-19-year age group recorded 40% (n = 1,009) of the total female rugby unionModerate-to-serious and serious (MSC) claims and 41% ($5,419,157 [AD$4,983,112]) of the total femalerugby union MSC costs. The knee was the most commonly recorded injury site accounting for 40.3%(n = 1,007) of MSC claims and 46.9% ($6,229,714 [AD$5,728732]) of MSC costs with an average cost of$1,245,943 ±$217,796 [AD$595,351 ±AD$104,070] per-year for female rugby union.Conclusions: This is the first study to report the nature and related costs for moderate-to-serious andserious injury claims for women`s rugby union in New Zealand. A total of 26,070 injury claims werelodged over the duration of the study but only 9.6% (n = 2,501) of these were classified as MSC injuryentitlement claims. Participants 25 years and older accounted for 31% of the female rugby union playerclaims. Females in the over 35-year age groups compete against younger participants which may accountfor the higher mean cost per-claim seen as the age groups increase in years until they retire from the game.